New Developments in Anarchist Studies - Lilley, P. J.; Shantz, Jeff (Book collections on Project MUSE., 2015)
Produced by the North American Anarchist Studies Network (NAASN), and edited by Jeff Shantz and P. J. Lilley, this volume comprises papers from NAASN's 5th Conference [La Red Norteamericana de Estudios Anarquistas / Le Réseau Nord-Américain d'études Anarchistes]. Anarchism is experiencing a remarkable resurgence in the new millennium. Not only active in the streets across Turtle Island, growing interest in anarchist scholarship is perhaps unprecedented. This is reflected in the development of the North American Anarchist Studies Network (NAASN). Drawn from papers presented at the fifth NAASN conference in Surrey (on Coast Salish Territories), this collection shows the vitality of contemporary anarchist research and writing.